2004
DOI: 10.1590/s0100-879x2004000500005
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between symptoms of the irritable bowel syndrome and the response to the food extract skin prick test

Abstract: The relationship between the irritable bowel syndrome (IBS) and food intolerance is not clear. We studied the cutaneous response to food antigens in 43 volunteers who were students and employees of the Faculty of Medicine of Universidade Federal Fluminense. Subjects were divided into 3 groups after evaluation for Roma II criteria for functional disease of the gastrointestinal tract: group I, 14 volunteers with IBS; group II, 15 volunteers with functional dyspepsia; group III, 14 volunteers without habitual gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…It is hypothesized that mucosal immune activation by FAs may contribute to the development of food allergy and IBS [9,11,13,[15][16][17]21,25] . Clinically, the role of food-intolerance-induced symptoms in IBS frequently contrasts with that in food allergy [20,[22][23][24][25]29,[37][38][39][40][41][42] , and dietary elimination may be associated with symptom improvement [31] . However, the interaction of food with the gastrointestinal system is not completely understood [13,17,20,22,23,25,29,[33][34][35][36][37]39] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that mucosal immune activation by FAs may contribute to the development of food allergy and IBS [9,11,13,[15][16][17]21,25] . Clinically, the role of food-intolerance-induced symptoms in IBS frequently contrasts with that in food allergy [20,[22][23][24][25]29,[37][38][39][40][41][42] , and dietary elimination may be associated with symptom improvement [31] . However, the interaction of food with the gastrointestinal system is not completely understood [13,17,20,22,23,25,29,[33][34][35][36][37]39] .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously noticed that IBS patients have greater cutaneous reactivity to FAs than to IAs, when compared to patients with functional dyspepsia or normal controls. An association between IBS and sensitivity to multiple foods and nonspecific response to SPTs has also been identified [30,42] . In the current study, the presence of diarrhea in IBS was a significant contributor to the greater cutaneous reactivity response to FAs.…”
Section: Discussionmentioning
confidence: 99%
“…30 It has been shown that the IBS patients have non-specific diet intolerance. 48 This lack of specificity causes considerable difficulty for IBS patients in choosing their diets. 48 There is a marked difference in opinions about the role of diet in IBS symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…48 This lack of specificity causes considerable difficulty for IBS patients in choosing their diets. 48 There is a marked difference in opinions about the role of diet in IBS symptoms. 30 The present study has not been designed or aimed at studying the diet IBS patients tolerate, but at studying the effect of diet management.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] Today IBS is considered a disorder of dysregulation of the so called brain-gut axis and there is evidence to also suggest that inflammation with the gastrointestinal tract may be of great importance in the majority of IBS patients. 22,23 Approximately 30% of patients with IBS identify acute infection as an initial trigger for their chronic intestinal infections. 17,18,21 These findings led to speculation that the immune system may play a role in the pathogenesis of at least a subpopulation of IBS patients.…”
Section: Introductionmentioning
confidence: 99%